Production and evaluation of survival of resistance structures of soilborne phytopathogenic fungi. - Bueno, César Júnior; Ambrósio, Márcia Michelle de Queiroz [UNESP]; de Souza, Nilton Luiz [UNESP] (My University, 2007)
Soilborne phytopathogenic fungi cause great losses in economical crops. These organisms produce resistance structures in the absence of hosts and / or under unfavorable climatic conditions. This allows the survival in soil for long period of time. When present, these structures make the pathogen control unfeasible. The objective of this work was to develop methodologies to produce and evaluate the survival of the resistance structures of Fusarium oxysporum f.sp. lycopersici race 2, Macrophomina phaseolina, Rhizoctonia solani AG4 HGI, Sclerotium rolfsii, Sclerotinia sclerotiorum, and Verticillium dahliae. The experiment was carried out in a randomized design, with 6 fungi per plot, 8 evaluation periods (0, 15, 30, 60, 90, 120, 150 and 180 days from the beginning of the experiment) and two conditions: field and laboratory. The structures of each fungus inside nylon bags (two replications) were buried in the field at 10 cm in depth for each evaluation, while in laboratory two flasks were maintained for each pathogen. The parameter evaluated was the fungal survival structures. All the methodologies developed showed positive results as the survival of the fungi in the field as well as in the evaluation of survival in lab conditions.
Produção e avaliação da sobrevivência de estruturas de resistência de fungos fitopatogênicos habitantes do solo
Keywords: Chlamydospore; Methodologies; Sclerotia; Soilborne fungi